Palladium on yttrium-embedded carbon nanofibers as electrocatalyst for oxygen reduction reaction in acidic media - Lee, Cheol-Ho; Park, Ha-Neul; Lee, Youn-Ki; Chung, Yong Sik; Lee, Sungho; Joh, Han-Ik (ELSEVIER SCIENCE INC, 2019)
Pd-Y alloy nanoparticle-embedded carbon nanofiber (CNF) were sequentially synthesized by electrospinning a solution mixture containing Y precursor and polyacrylonitrile, stabilization, carbonization at 1200 degrees C, activation, and impregnation of Pd. The CNF acted as catalytic supports and templates, retaining the nanoparticle size at high temperatures; under these conditions, other nanomaterials would easily aggregate or sinter. To expose the surface of Y nanoparticles embedded into the CNF (Y-ACNF), mild and selective oxidation was conducted. The impregnated Pd exhibited the excellent degree of alloying with and dispersion on Y-ACNF, leading to outstanding activity with four-electron reaction of Pd-3/Y-ACNF for oxygen reduction reaction comparable to commercial platinum-based catalysts.
Keywords: CATALYSTS; METAL; NANOPARTICLES; PLATINUM; ALKALINE; ALLOYS; ORR